A Study on the Awareness and Preventive Measures Against Scams in Friendship Based Social Networking Apps among young adults - Nivedha , R.; Nevis Soris, N. Maria (Journal of Neonatal Surgery, 2025)
With the rise of social media platforms and the digital revolution, new deceptive marketing strategies have emerged. This study examines the two threats presented by online frauds disguised as gambling apps and the significant role social media promoters play in promoting these apps among young people. These promotions frequently hide the dangers of gambling and financial loss by presenting products as harmless entertainment or chances for quick cash. Social media promoters frequently promote these apps through paid content and effective marketing, greatly increasing their impact by taking use of their wide audience and perceived authenticity. Young adults are especially at risk because of things like their status as digital natives, their desire for rapid financial gain, and their vulnerability to aspirational content from well-known online promoters. This study focuses on how promoters promote these apps, how they affect young users financially and psychologically, and whether these promotions are considered manipulative or scam-like behaviour. By examining recent case studies, qualitative research, and regulatory responses, this paper evaluates how well influencer marketing shapes youth perceptions, the workings of digital gambling scams, and the urgent requirement for strengthened regulations and digital literacy programs to safeguard vulnerable groups from changing online threats. It is expected that the results will add to the conversation on ethical influencer marketing and promotions, consumer protection, and the need for stronger laws governing digital advertising that target misleading advertising